Tracking Carbon in Executive Trains: A Study of Non-Traction Electricity and CO₂ Emissions in the Bima Train, Indonesia - Yudi Utomo Putra; Dwinugroho Putro Utomo (Jurnal Konversi Energi dan Manufaktur, 2026)
Non-traction electricity consumption in train operations includes auxiliary loads such as lighting, air conditioning (AC), power outlets, and other electronic devices are essential for passenger comfort and safety. Although smaller than traction energy, the carbon emissions from non-traction electricity consumption remain significant, particularly when electricity is supplied by fossil-fueled diesel generators. This study quantifies the total annual CO₂ emissions generated from non-traction electricity used in executive-class train cars applying a quantitative approach based on measured energy consumption and emission factors. Data analyzed include electrical energy consumption (kWh), daily operating duration and frequency, and the annual operating period of a single train set as the unit of analysis. Emission calculations were performed using an emission factor of 0.64–0.74 kg CO₂/kWh for diesel generator-based systems, incorporating operational assumptions such as constant AC usage and auxiliary load patterns. Sensitivity analyses to evaluate the effect of variations in operating patterns. Results indicate that total annual CO₂ emissions range from 511 to 591 Tons per train, with AC identified as the dominant contributor to non-traction energy use. Scenario simulations suggest that integrating renewable energy sources, particularly solar panels, combined with targeted energy efficiency improvements, can reduce non-traction emissions by approximately 25–40% compared to current operational conditions. Thus, effective management of non-traction energy is a critical component of railway decarbonization, and implementing renewable energy solutions alongside efficiency-based strategies offers a substantial opportunity to reduce operational emissions, supporting sustainable railway operations and contributing to Indonesia’s net zero emissions target by 2060.